MicroRNA Profile to Predict Gemcitabine Resistance in Bladder Carcinoma Cell Lines - Kozinn, Spencer I. (SAGE Publications, 2013)
MicroRNAs (miRNA) are small, noncoding RNAs with important regulatory roles in development, differentiation, cell proliferation, and death as well as the complex process of acquired drug resistance. The goal of this study was to identify specific miRNAs and their potential protein targets that confer acquired resistance to gemcitabine in urothelial carcinoma of the bladder (UCB) cell lines. Gemcitabine-resistant cells were established from 6 cell lines following exposure to escalating concentrations of the drug and by passaging cells in the presence of the drug over a 2- to 3-month period. Differential miRNA expression was identified in a microarray format comparing untreated controls with resistant cell lines, representing the maximum tolerated concentration, and results were validated via qRT-PCR. The involvement of specific miRNAs in chemoresistance was confirmed with transfection experiments, followed by clonogenic assays and Western blot analysis. Gemcitabine resistance was generated in 6 UCB cell lines. Microarray analysis comparing miRNA expression between gemcitabine-resistant and parental cells identified the differential expression of 66 miRNAs. Confirmation of differential expression was recorded via qRT-PCR in a subset of these miRNAs. Within this group, let-7b and let-7i exhibited decreased expression, while miR-1290 and miR-138 displayed increased expression levels in gemcitabine-resistant cells. Transfection of pre–miR-138 and pre–miR-1290 into parental cells attenuated cell death after exposure to gemcitabine, while transfection of pre–miR-let-7b and pre–miR-let-7i into the resistant cells augmented cell death. Mucin-4 was up-regulated in gemcitabine-resistant cells. Ectopic expression of let-7i and let-7b in the resistant cells resulted in the down-regulation of mucin-4. These results suggest a role for miRNAs 1290, 138, let-7i, and let-7b in imparting resistance to gemcitabine in UCB cell lines in part through the modulation of mucin-4. Alterations in these miRNAs and/or mucin-4 may constitute a potential therapeutic strategy for improving the efficacy of gemcitabine in UCB.